Adjustment of Physiognomy in Children with Down Syndrome - K. Nováková; B. Polášková; E. Fritschová; K. Langová (Czech Dental Chamber, 2006)
The aim of the work was to evaluate the possibility to adjust physiognomy of children with Down syndrome and to create our own modification of the Castillo-Morales method. The cohort included 25 children at the age of 0.5 to 8.22 years and the mean age of 2.79 year. The position of tongue was evaluated in 5 variations, the time of opened mounth for the period of 2 minutes and the lip occlusion in 4 variants in the entry examination and at the end of treatment of dispensary. The therapy was started by a logopedist with individually aimed logopedic exercise, originating in the principles of developmental therapy of neuromotoric skills and digital stimulation of selected points of the face. Pediatric stomatologist applied the exercise by confection vestibular screen, indicated an individual palatal plate with adequate stimulation elements according to age with two oval symmetric resin pelotae: protrusion of the tongue (in entry examination protruding from the mouth in 40% of children) was adjusted in all subjects at the end of the treatment. The long-term opened mouth was observed in 56% of the cohort during the entry examination, but in one child only at the end of dispensary. The permanently closed mouth was detected in the entry examination in 4% of the cohort and in 64% of them at the end of dispensary. A free lip occlusion (in 76% during the entry examination) was markedly adjusted (present in 12% of the cohort at the end of dispensary) and the ability to purse one's lips was increased from 4% of the cohort in entry examination to 56% of the cohort at the end of dispensary.It has been proved that the adjustment of physiognomy in children is possible not only at the suckling age, but it is more demanding: the extended complex therapy originating in the Castillo-Morales method, acupressure exercise, myofunctional therapy, special logopedic knowledge, vestibular screen and general muscular (aerobic) excecise.